THE MEDIATING ROLE OF INNOVATION: ORGANIZATIONAL LEARNING. - Pratiwi, Deifa Arshanti; Fanani, Zainal (Universitas Muhammadiyah Malang)
The aim of this study is to examine the mediating role of innovation on the relationship of organizational learning to company performance. This type of research is quantitative research that uses an explanatory approach. The data used in this study are primary data in the form of a questionnaire distributed to managers of the company's business units in the industrial area of PT. Surabaya Industrial Estate Rungkut. The sample in this study was 205, which was determined using purposive sampling technique. Data were analyzed using Structural Equation Modeling (SEM) with the Partial Least Square approach. The results of the study indicate that innovation can mediate the influence of organizational learning on company performance.Â